10 Electrocardiographic predictors of torsadogenic risk during dofetilide or sotalol initiation: utility of a novel T wave analysis programme. (7th October 2015) - Sugrue, A; Kremen, V; Qiang, B; Sheldon, S; DeSimone, C; Asirvatham, S; Friedman, P; Ackerman, M; Noseworthy, P
Abstract : Background: Initiation of class III anti-arrhythmic medications requires telemetric monitoring for ventricular arrhythmia and QT prolongation to reduce the risk of torsades de pointes (TdP). Heart rate corrected QT interval (QTc) is an indicator of risk, however it is imperfect and more subtle abnormalities of repolarization have been linked with arrhythmogenesis. We developed and tested a novel T wave analysis tool to identify electrocardiographic predictors of torsadogenic risk. Methods and results: We retrospectively identified patients admitted to Mayo Clinic for initiation of dofetilide or sotalol who developed drug induced-TdP. The immediate pre-TdP or hospital discharge surface electrocardiogram (ECG) was compared between cases and controls using a novel T wave program that quantified subtle changes in T wave morphology. We identified 13 TdP cases and 26 matched controls (age and sex matched). The QTc and 12 T wave parameters were able to distinguish TdP cases from controls. The top performing parameters were the QTc in lead V3 (mean case vs control 480 vs 420 msec, p < 0.001, r = 0.72) and T wave right slope in lead I (mean case vs control –1668.71 vs –840.29 mV/ms, p = 0.002, r = 0.45). The addition of T wave right slope to QTc improved prediction accuracy from 79 to 88%. Conclusion: Our data demonstrates that, in addition to QTc, the T wave right slope is correlated strongly with TdP risk. This suggests that a computer-based repolarization measurement tool that integrates additional data beyond the QTc may identify patients with the greatest torsadogenic potential.